The Mediating Role of Engagement and Culture in the Relationship Between Paternalism, Organizational Identification and Voice Behavior - Allouzi, Hala; Yucel, Recep (European Scientific Journal, ESJ, 2025)
This study investigates the mediating effects of work engagement and organizational culture in the relationship between paternalistic leadership, organizational identification, and voice behavior within the context of Jordanian industrial shareholding companies. The research sample was drawn from a population of 3,612 managers occupying top and mid-level positions across 239 companies, as listed by the Jordanian Ministry of Industry and Trade. For the purposes of this research, large firms were classified as those with a workforce of 500 employees or more. A stratified random sampling technique was adopted to enhance sample representativeness, resulting in a calculated minimum sample size of 347 respondents. From the 400 questionnaires distributed, 347 were returned, of which 318 were deemed suitable for statistical analysis, corresponding to a valid response rate of 79.5%. A quantitative research design was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software to test the hypothesized relationships. The results revealed that paternalistic leadership has a significant and direct positive effect on both organizational identification and voice behavior. Similarly, organizational culture demonstrated a substantial positive influence on these outcomes. Moreover, work engagement was found to be positively correlated with organizational identification and voice behavior. Importantly, the analysis confirmed the mediating roles of both organizational culture and work engagement. Specifically, organizational culture mediated the relationship between paternalistic leadership and both organizational identification and voice behavior. Additionally, work engagement served as a mediator in the relationship between paternalistic leadership and these two dependent variables. These results highlight the pivotal role of internal organizational dynamics - namely culture and employee engagement - in strengthening leadership effectiveness and fostering constructive employee behavior in industrial organizations operating in Jordan.